A Study of the Water Resources Potential of the Sewan River in East Sarmi District, Sarmi Regency - Gedrida Yacoba Maay; Mujiati Mujiati; Harmonis Rante; Bahtiar Bahtiar; Janviter Manalu (Journal of Social Research, 2025)
Access to clean water is a fundamental need for supporting healthier and cleaner living conditions, which is critical for achieving the Millennium Development Goals (MDGs). In East Sarmi District, Sarmi Regency, the community relies on surface water, groundwater, and untreated rainwater as primary sources of raw water. This study aims to evaluate the potential of these water sources to meet health standards and the community's future water needs. The research focuses on the condition of the Sewan River, a significant water source in East Sarmi District, and its capacity to fulfill the clean water demands. The study uses SWOT analysis to assess the potential of the Sewan River as a reliable source. The findings reveal that the required clean water in Sarmi District by 2043 is 1.46 liters/second, which is equivalent to 0.0016 m³/day. The Sewan River currently provides 198 liters/second, indicating that its water supply is more than sufficient to meet future needs. Furthermore, both the community and the local government support the development of water resources in the region. This research contributes to identifying sustainable water sources and offers recommendations for improving water management in East Sarmi District to meet health standards and enhance the quality of life.